EXPLORING THE DIGITAL AND ENTREPRENEURSHIP SKILLS REQUIRED BY MARKETING STUDENTS OF IGNATIUS AJURU UNIVERSITY OF EDUCATION FOR EMPLOYABILITY (UNIZIK Journal of Marketing, 2025)
The rapid digitalization of business and the growing importance of entrepreneurship have reshaped employability requirements for university graduates, particularly in Marketing department. This study explored the digital and entrepreneurship skills required by Marketing students of Ignatius Ajuru University of Education, Port Harcourt, to enhance employability. Specifically, the study examined how social media marketing skills and entrepreneurial skills influence employability outcomes. A cross-sectional survey design was adopted, with 200 marketing students purposively sampled across different levels of study. Data were collected using a structured questionnaire titled Digital and Entrepreneurship Skills for Employability Index (DESEI) and analyzed using Spearman’s Rank Correlation at a 0.05 level of significance. Findings revealed a significant positive relationship between social media marketing skills and employability (r = 0.715, p < 0.05), as well as between entrepreneurial skills and employability (r = 0.702, p < 0.05). The results indicate that proficiency in social media marketing enhances students’ visibility, engagement, and adaptability in modern marketing contexts, while entrepreneurial skills equip them to identify opportunities, innovate, and achieve self-reliance. The study recommends integrating practical digital and entrepreneurship training into the Marketing curriculum, establishing institutional support structures such as incubation centers, and promoting experiential learning opportunities to better prepare graduates for the dynamic labor market.
Keywords: Career Development, Digital Communication, Digital Skills, E-commerce Skills, Employability, Marketing Students